GUIDANCE AND CONTROL SYSTEM FOR SURFACE-TO-AIR MISSILE - Fabian Koswara, Steven
Missile is one of the most effective air defense weapon against fighter jets. However, as technological advancement enabled fighter jets to become faster and more maneuverable, missile technology must also be improved, especially on guidance and flight control systems. In this thesis, guidance and control system of a homing missile is developed. There are three main components in a modeling of a homing missile, which are guidance system, flight control system, and missile flight dynamics. The guidance system is developed on proportional navigation guidance law. The control system is developed using linear quadratic regulator method. Missile flight dynamics are derived from dynamics of conventional aircraft. First, mathematical models of the guidance system, control system, and missile flight dynamics are developed. Based on the previous mathematical models, a numerical simulation model is developed on Simulink platform. Missile stability characteristics are obtained from Missile Datcom using AIM-120 AMRAAM as the reference parameters. The guidance system produces a command acceleration that must be followed by the control system. The control system uses missile flight parameters as feedback to control the acceleration produced by the missile dynamics. After the numerical simulation model is developed, five three-dimensional engagement scenarios are executed. Then, an analysis is done on the simulation results, including miss distance, engagement time, trajectory, missile acceleration, and control surface deflections. The simulation results showed that the guidance and control system developed has been able to successfully engage targets under the given scenarios. However, there are also a few problems such as sudden surge in acceleration within a very short period.